Effect of porous orthopaedic implant material and structure on load sharing with simulated bone ingrowth: A finite element analysis comparing titanium and PEEK. (April 2018) - Carpenter, R. Dana; Klosterhoff, Brett S.; Torstrick, F. Brennan; Foley, Kevin T.; Burkus, J. Kenneth; Lee, Christopher S.D.; Gall, Ken; Guldberg, Robert E.; Safranski, David L.
Abstract: Osseointegration of load-bearing orthopaedic implants, including interbody fusion devices, is critical to long-term biomechanical functionality. Mechanical loads are a key regulator of bone tissue remodeling and maintenance, and stress-shielding due to metal orthopaedic implants being much stiffer than bone has been implicated in clinical observations of long-term bone loss in tissue adjacent to implants. Porous features that accommodate bone ingrowth have improved implant fixation in the short term, but long-term retrieval studies have sometimes demonstrated limited, superficial ingrowth into the pore layer of metal implants and aseptic loosening remains a problem for a subset of patients. Polyether-ether-ketone (PEEK) is a widely used orthopaedic material with an elastic modulus more similar to bone than metals, and a manufacturing process to form porous PEEK was recently developed to allow bone ingrowth while preserving strength for load-bearing applications. To investigate the biomechanical implications of porous PEEK compared to porous metals, we analyzed finite element (FE) models of the pore structure-bone interface using two clinically available implants with high (> 60%) porosity, one being constructed from PEEK and the other from electron beam 3D-printed titanium (Ti). The objective of this study was to investigate how porous PEEK and porous Ti mechanical properties affect load sharing with bone within the porous architectures over time. Porous PEEK substantially increased the load share transferred to ingrown bone compared to porous Ti under compression (i.e. at 4 weeks: PEEK = 66%; Ti = 13%), tension (PEEK = 71%; Ti = 12%), and shear (PEEK = 68%; Ti = 9%) at all time points of simulated bone ingrowth. Applying PEEK mechanical properties to the Ti implant geometry and vice versa demonstrated that the observed increases in load sharing with PEEK were primarily due to differences in intrinsic elastic modulus and not pore architecture (i.e. 4 weeks, compression: PEEK material/Ti geometry = 53%; Ti material/PEEK geometry = 12%). Additionally, local tissue energy effective strains on bone tissue adjacent to the implant under spinal load magnitudes were over two-fold higher with porous PEEK than porous Ti (i.e. 4 weeks, compression: PEEK = 784 ± 351 microstrain; Ti = 180 ± 300 microstrain; and 12 weeks, compression: PEEK = 298 ± 88 microstrain; Ti = 121 ± 49 microstrain). The higher local strains on bone tissue in the PEEK pore structure were below previously established thresholds for bone damage but in the range necessary for physiological bone maintenance and adaptation. Placing these strain magnitudes in the context of literature on bone adaptation to mechanical loads, this study suggests that porous PEEK structures may provide a more favorable mechanical environment for bone formation and maintenance under spinal load magnitudes than currently available porous 3D-printed Ti, regardless of the level of bone ingrowth. Graphical abstract: fx1 Highlights: Evaluated load sharing with bone ingrowth in porous PEEK & porous Ti using FEA. Porous PEEK increased load sharing with ingrown bone compared to porous Ti. Porous Ti produced low strains implicated in stress-shielding & bone resorption. Lower modulus of porous PEEK may support bone formation at spinal load magnitudes.